FICTIONAL MINDLESSNESS AND THE PROBLEM OF UNREPORTABILITY - VLADIMIR VUJOŠEVIĆ (Manuscrito)
Abstract When we engage with fictions, we are, in effect, pretending to deal with reports of actual events. After all, numerous fictional works are explicitly designed to facilitate this kind of pretense. This was the prevailing understanding of fiction in both analytic philosophy and classical narratology for decades. However, there is a significant problem with this view: many fictional narratives routinely portray scenarios that could not possibly be the subject of anyone’s reporting. Currie’s 'mindless fictions' are one such example. This issue can be referred to as the problem of unreportability. The standard solution to this challenge has been to argue that fictions are not pretend reports, but rather direct authorial stipulations to imagine specific scenarios. This paper contends, however, that such an explanation fails to provide a satisfactory account of fiction. By drawing on Walton’s notion of ‘silly questions’, it instead argues for a revised version of the report model-one that doesn’t necessarily depend on ubiquitous fictional reporters.